GAYA KEPEMIMPINAN DEMOKRATIS PERPUSTAKAAN KOTA YOGYAKARTA (STUDI KASUS) - Sri Utari; Moh. Mustofa Hadi (Jurnal Pustaka Ilmiah, 2020)
The library is a non-profit institution engaged in services and services that are directly related to the community. In order to regulate the rhythm of work continuity, a library organization has a leader, namely the head of the library. The head of the library has a way of leading or often called style, to run a library. Leadership style is the way a leader influences subordinates in running an organization. One type of library is the public library. Sustainability of public libraries will work well requires leaders. Library leaders generally have their own style to carry out their leadership. This research discusses how the leadership style in public libraries? Case study in Yogyakarta City Public Library. The research method used is using literature study, semi-structured interviews, and library observations. The conclusion obtained is that the leadership of the Yogyakarta City Library has a demoratic leadership style. This is evident from every time a decision is made, the head of the library involves staff to submit suggestions and input for the sustainability of the library. These suggestions and input are used as a decision maker. The final result of the decision remains in the hands of the head of the library.